Formulation and Evaluation of Floating Tablets of Diltiazem Employing Olibanum Gum - Chowdary, K.P.R.; Galibsaheb, V. (Asian Journal of Chemistry, 2010)
The objective of the study is to formulate and evaluate floating tablets of diltiazem employing olibanum gum, a natural gum resin in comparison to HPMC K15M, a synthetic cellulose derivative. Floating tablets of diltiazem were prepared employing olibanum gum and HPMC, K15M as matrix formers, sodium bicarbonate as gas generating agent and bees wax as floating enhancer and the tablets were evaluated for in vitro buoyancy and drug release characteristics. Tablets formulated employing olibanum gum (50 %), sodium bicarbonate (10 %) and bees wax (10 %) exhibited floating over 48 h with a floating lag time of 5-10 min. Diltiazem release from the floating tablets formulated was slow, spread over more than 24 h and depended on the polymer used and its strength and concentration of sodium bicarbonate in the tablets. Drug release was diffusion controlled and followed first order kinetics. Fickian diffusion was the drug release mechanism from all the tablets formulated. Olibanum gum gave slow, controlled and complete drug release in 24 h, whereas HPMC, K15M gave slow but incomplete drug release. Olibanum was found to be a better matrix former than HPMC for floating tablets. Since olibanum gum is of natural origin, it is non-toxic, biocompatible and cheaper.